2019
DOI: 10.1080/03007995.2019.1631058
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation and switching of biologics in ulcerative colitis: a systematic literature review in real-world evidence

Abstract: Background: Biologics used to treat ulcerative colitis (UC) may lose their effect over time, requiring patients to undergo dose escalation or treatment switching, and systematic literature reviews of realworld evidence on these topics are lacking. Aim: To summarize the occurrence and outcomes of dose escalation and treatment switching in UC patients in real-world evidence. Methods: Studies were searched through MEDLINE, MEDLINE IN PROCESS, Embase and Cochrane (2006-2017) as well as proceedings from three maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
(101 reference statements)
1
21
1
Order By: Relevance
“…Suboptimal response indicators could be utilized to estimate the effective and safe use of biologics in the realworld. [16][17][18][19][20] However, only limited data are available on suboptimal responses to anti-TNF therapy among UC patients in Asia, especially in the era of biologics other than nonanti-TNFs. 21,22 We aimed to identify suboptimal responses to anti-TNF therapies and differences between anti-TNF agents for UC patients in Korea using nationwide population-based data.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal response indicators could be utilized to estimate the effective and safe use of biologics in the realworld. [16][17][18][19][20] However, only limited data are available on suboptimal responses to anti-TNF therapy among UC patients in Asia, especially in the era of biologics other than nonanti-TNFs. 21,22 We aimed to identify suboptimal responses to anti-TNF therapies and differences between anti-TNF agents for UC patients in Korea using nationwide population-based data.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several authors have proposed that the DI requirement, which has been shown to recapture the response in multiple studies [ 187 ], would be a more objective and reliable measure [ 188 ] and, therefore, a useful surrogate for the LOR. Several reviews have previously assessed the incidence of a LOR, mainly in CD [ 185 , 186 , 187 , 188 , 189 , 190 , 191 ]. When compared to previous reviews, our study includes a considerably higher number of studies, up to January 2020, assessing both UC and CD patients and, therefore, conferring more robustness and reliability to our work.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have estimated that approximately one-third of inflammatory bowel disease patients experience LOR and require DI, and that occurs more frequently in patients with prior anti-TNF exposure [ 188 , 189 , 190 , 191 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported the most common switching pattern, infliximab to adalimumab, occurred in 3.8% (median 5.6 years) to 25.5% (mean 3.3 years) of patients. 31 A US study reported switch rate to another biologic ranged from 4.5% to 20%. 32 About 20.0% of patients switched to other biologic in our study.…”
Section: Open Accessmentioning
confidence: 99%